Implementation and Problematic of Blended Learning in Fiqh Learning: A Combination of Synchronous and Asynchronous in Online Learning - Muhammad Nurul Mubin; Muhammad Sya'dullah Fauzi; Ahmad Saufi Al Hadisi; Achmad Bayhaqi; Moh. Faza Rosyada (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This article aims to analyze how the implementation and problems of Blended Learning learning in fiqh courses are carried out in the Islamic Religious Study department at UIN Sunan Kalijaga Yogyakarta. The subjects research were students of P Islamic Religious Study of the second semester. Data collection through observation, online interviews via a google form, and documentation from related literature. The results showes that The implementation of the Blended Learning method of learning is done by combining the Synchronous model using the Zoom Meeting and Google Meet platforms, and Asynchronous using the e-learning platform. Some problems in blended learning include problems with internet network disturbances and limited quotas, disturbances in the learning environment, difficulty in finding references, and some students who feel they do not understand the material. So it is necessary to solve problems related to external and internal factors in the learning process. Mastery of technology and environmental conduciveness is essential for students. In addition, lecturers must also be able to manage classes by adjusting online learning conditions as well as possible. Keywords: Blended Learning, Combination Synchronous Asynchornous, Online Fiqh Learning